Los impactos de la Inversión Extranjera en el sector minero y energético en Colombia de 1991 -2011 (2013)
The present research work aims to discover the concept of foreign investment, implementation and current regulations applicable in Colombia, participation rates in the sectors of the economy with particular emphasis on mining and energy sector, to where they will to break down the potential environmental impact, infrastructure and human causes lack of control over the activities of foreign firms in the country.